Herbal handmade products for animal treatment - Silva, Juciely Gomes da; Jerônimo, Rayane Ellen de Oliveira; Azevedo, Camila Firmino de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Since the beginning, man has used plants and natural products, due to their high potential for prevention and cure of the main affections affected to them. Medicinal plants can also be used to treat animals, in natura or transformed into different types of preparations, being considered as a safe, viable and low-cost alternative, especially for family farmers, since it reduces the use of synthetic medicines. Thus, the aim of this study was to prepare different artisanal products based on medicinal plants for animal use, as well as to encourage and promote the use of natural products in the treatment and prevention of diseases in animals. Soaps, ointments and handmade oils were produced at the Biology Laboratory on Campus II of the State University of Paraíba. These products were distributed with farmers, tutors and animal protection entities, in addition to being exhibited at scientific and cultural events, together with seedlings of medicinal species and informative folders on the subject. The preparation and distribution of these products, in addition to the distribution of seedlings and informative folders, appear as a way to disseminate knowledge about safe and rational use and encourage the cultivation and use of plants in animal treatment.